The Effect of Axial Length Elongation on Corneal Biomechanical Property - Liu, Guihua; Rong, Hua; Zhang, Ping; Xue, Yu; Du, Bei; Wang, Biying; Hu, Jiamei; Chen, Zhi; Wei, Ruihua (Frontiers in Bioengineering and Biotechnology, 2021)
Background: To investigate the correlation between the corneal biomechanical parameter stress-strain index (SSI) and axial length (AL) in non-high myopia (NHM) and high myopia (HM). Methods: This study included 117 eyes from 117 participants. Among them, 59 (50.4%) had NHM and 58 (49.6%) had HM. AL was measured using Lenstar LS-900, and central corneal thickness (CCT) and anterior chamber volume (ACV) were measured using Pentacam. The SSI was measured via corneal visualisation Scheimpflug technology (Corvis ST). Kolmogorov-Smirnov test, Student’s t-test, and Pearson and partial correlation analyses were used for statistical analyses. Results: The mean (±SD) SSI was 1.08 ± 0.15 in the NHM group and 0.92 ± 0.13 in the HM group (P<0.01). SSI was positively correlated with age (NHM: r=0.326, P<0.05; HM: r=0.298, P<0.05) in both the groups and negatively correlated with AL (r=-0.476, P<0.001) in the NHM group but not in the HM group (P>0.05). CCT was negatively correlated with AL (r=-0.289, P<0.05) and ACV positively correlated with AL (r=0.444, P<0.001) in the NHM group. However, neither CCT nor ACV was correlated with AL (P>0.05) in the HM group. Conclusions: Corneal biomechanical parameter SSI was worse in the HM group than in the NHM group. When analyzed separately, SSI was negatively correlated with AL in the NHM group, but not in the HM group, which may provide insight into different ocular growth patterns between the two groups.